2010
DOI: 10.1007/s10562-010-0345-9
|View full text |Cite
|
Sign up to set email alerts
|

On the Product Formation in 1-Butene Metathesis over Supported Tungsten Catalysts

Abstract: 1-Butene metathesis was performed over 8 wt% tungsten catalysts supported on silica, silica-alumina and c-Al 2 O 3 . Under the applied reaction conditions, 1-butene metathesis yields with a relatively large selectivity iso-butene in addition to the expected metathesis products. The isobutene selectivity is high for catalysts with a relative low activity and decreases with increasing metathesis activity. It is deduced that iso-butene formation involves surface tungsten complexes, whose formation inhibits the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…5B). Bands at 1446, 1490 and 1610 cm -1 are associated to pyridine coordinated to Lewis acid sites, while bands at 1535 and 1638 cm -1 are related to pyridinium cations in Brönsted acid sites [48] (Fig. 5B).…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…5B). Bands at 1446, 1490 and 1610 cm -1 are associated to pyridine coordinated to Lewis acid sites, while bands at 1535 and 1638 cm -1 are related to pyridinium cations in Brönsted acid sites [48] (Fig. 5B).…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…[39] For pure SBA-15, there is no evidence of the band (not in the figure). The sample tungsten incorporated into the framework, WO 3 -SBA-15 (30), shows a similar band at 230 nm can be attributed to the presence of isolated [WO 4 ] 2À tetrahedral species. The second band at 290 nm may be assigned to isolated tungsten species or low-condensed oligomeric tungsten oxide species.…”
mentioning
confidence: 82%
“…[27,28] There are several studies describing the production of propylene by 1-butene metathesis. [26,29,30] However, 1-butene is expensive as compared to 2-butene because 1-butene has a huge demand as a monomer for the production of liner low density polyethylene (LLDPE) and polybutene. [31] To the best of our knowledge, there is no communication dealing with the application of tungsten oxide containing mesoporous silica (WO 3 -SBA-15) as a catalyst for 2-butene metathesis reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] It has been suggested that autometathesis of 1-butene, that is, isomerization of 1-butene into 2-butene followed by cross-metathesis of 1-butene and 2-butene, shouldb eamore attractive and promising wayt oe nhance the productivityo fp ropene as ar esult of the abundance of butene as af eedstock in the petrochemical industry. [10][11][12][13][14][15] Usually,traditional porousalumina,silica, or their composites are applied as supportsd uring the preparation of metathesis catalysts. For example, Wang et al [11] studied the autometathesis of 1-butene on aW O 3 /SiO 2 catalystu nder the reactionc onditions of 350 8C, weight hourly space velocity( WHSV) = 0.36 h À1 ,a nd 0.5 MPa, and an initial propene yield of 32.7 % was obtained.H armase et al [15] deposited Ws pecies on acidic alumina-silica composite supports, and am aximum propene yield of 31.6 %w as realized at 450 8Ca nd 0.085 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] Usually,traditional porousalumina,silica, or their composites are applied as supportsd uring the preparation of metathesis catalysts. For example, Wang et al [11] studied the autometathesis of 1-butene on aW O 3 /SiO 2 catalystu nder the reactionc onditions of 350 8C, weight hourly space velocity( WHSV) = 0.36 h À1 ,a nd 0.5 MPa, and an initial propene yield of 32.7 % was obtained.H armase et al [15] deposited Ws pecies on acidic alumina-silica composite supports, and am aximum propene yield of 31.6 %w as realized at 450 8Ca nd 0.085 MPa. Recently, Mazoyer et al [13] developed ac atalyst with tungsten hydride supported on alumina (WH 3 /Al 2 O 3 )t hrough as urfaceo rganometallicc hemistry method.T his method allowed better molecular design of the active site, and preferable propene productivity was obtained in the autometathesis of 1-butene.…”
Section: Introductionmentioning
confidence: 99%